Did Transformational Leadership Elitist and Antidemocratic? A Literature Review - Agus Purwanto; Sekundina Wiliana Kusumaningsih; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
In this study we aim to explore and determine whether transformational leadership is elitist and anti-democratic. The purpose of writing this article is to conduct a systematic literature review on 6 (six) articles of leadership models from reputable international journals. The method used is a systematic literature review of 6 articles published in reputable international journals that discuss leadership models in secondary and higher education institutions in education 4.0 era. The results of the systematic literature review show that the leadership models of transformational that have a positive and significant effect on the performance of educational institutions. In order to see the link with transformational leadership, organize a literature review to locate relevant literature and extract knowledge about elitism and democratic leadership. Transformational leadership is not elitist and anti-democratic. It’s empowering the employee to encouraging inspiration, idealized power, intellectual stimulation and individual judgment. It engages workers through participatory, support for new ideas and a substantial degree of flexibility and autonomy for be pro-active and take risks, also rely heavily on communication and relationships. This research only to find out whether transformational leadership is indeed elitist and anti-democratic based on a literature review and for empirical evidence further study is needed. The relation between transformational leadership and member responses to organizational change has been empirically validated by numerous studies